Traumatic brain injury patient volume and mortality in neurosurgical intensive care units: a Finnish nationwide study - Raj R; Bendel S; Reinikainen M; Hoppu S; Luoto T; Ala-Kokko T; Tetri S; Laitio R; Koivisto T; Rinne J; Kivisaari R; Siironen J; et al. (BIOMED CENTRAL LTD, 2022)
Background: Differences in outcomes after traumatic brain injury (TBI) between neurosurgical centers exist, although the reasons for this are not clear. Thus, our aim was to assess the association between the annual volume of TBI patients and mortality in neurosurgical intensive care units (NICUs).Methods: We collected data on all patients treated in the five Finnish university hospitals to examine all patients with TBI treated in NICUs in Finland from 2009 to 2012. We used a random effect logistic regression model to adjust for important prognostic factors to assess the independent effect of ICU volume on 6-month mortality. Subgroup analyses were performed for patients with severe TBI, moderate-to-severe TBI, and those who were undergoing mechanical ventilation or intracranial pressure monitoring.Results: Altogether 2,328 TBI patients were treated during the study period in five NICUs. The annual TBI patient volume ranged from 61 to 206 patients between the NICUs. Univariate analysis, showed no association between the NICUs' annual TBI patient volume and 6-month mortality (p = 0.063). The random effect model showed no independent association between the NICUs' annual TBI patient volume and 6-month mortality (OR = 1.000, 95% CI = 0.996-1.004, p = 0.876). None of the pre-defined subgroup analyses indicated any association between NICU volume and patient mortality (p > 0.05 for all).Discussion and Conclusion: We did not find any association between annual TBI patient volume and 6-month mortality in NICUs. These findings should be interpreted taking into account that we only included NICUs, which by international standards all treated high volumes of TBI patients, and that we were not able to study the effect of NICU volume on neurological outcome.